Perencanaan partisipatif taman tematik Perumahan Kampoeng Semawis Semarang - Thomasonan Lutfie Prananto; Wulandari, Astari; Hetyorini (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
This community service focuses on participatory planning of thematic parks at the Kampoeng Semawis Housing Complex, Semarang. This area has great potential to be developed into a useful public space, but currently the existing green open space is still less than optimal in its use. The focus of this service is to create a thematic park that not only functions as a green open space, but also as a place for social interaction and education for residents. The main issue faced is the lack of community involvement in planning and managing public spaces, which results in a lack of sense of ownership and concern for existing facilities. Through a participatory approach, this program aims to increase citizen participation in planning and managing public spaces. It is hoped that with this thematic park, the level of citizen participation in maintaining and utilizing public spaces will increase, which will ultimately improve the quality of life for the residents of Kampoeng Semawis. This community service aims to examine the participatory planning process for thematic parks in Kampoeng Semawis and its impact on community participation and the quality of life of local residents. It is hoped that the results of this program can become a model for the development of public space in other residential areas in Semarang.